Normese en la ley orgánica de servicio público LOSEP la interposición administrativa al sumario administrativo. - Moreno Moreno, Ximena Gabriela (2018)
The Constitution of the Republic of Ecuador, in its normative issues substantive criteria for the protection of the rights enshrined Ecuadorian society, especially the government and those administrative system depend on the state, respect of and public servants, whose specific mission is to provide the direct protection and immediate of the rights recognized in the Constitution where there is infringement of such rights by acts or omissions of any non-judicial public authority if the person concerned is in a subordinate position, helplessness or discrimination, a problem that is evident in the conduct of administrative proceedings; that problems arising between public servants and government administration should be resolved through contentious - administrative and it also operates when these problems cause certain legal rights are affected; before this procedure because there is confusion about the proper way to deal with the violation of the rights of public servants for administrative acts; before this, I consider of importance that is established as an enabling and substantial procedure, the Administrative interposition by the competent authority and leadership of the labor relations in Ecuador such as the Ministry of Labour Relations, filing consisting of the challenge to a process that has the special character in terms of procedure, which generally proposes or puts the managed, ie the state, so that the Administrative Court does not become a conflict that arises when these legal rights are confused with fundamental rights and brandishing this argument shares administrative defense arise via immediate protection and protection of the rights of the citizens as are the and public servants in Ecuador, not the very essence of all administrative formalities denature, and administrative law in our country is guaranteed.